Analysing architecture - Unwin, Simon, 1952- (London ; New York : Routledge, 2014)
"Now in its fourth edition, Analysing Architecture has become internationally established as the best introduction to architecture. Aimed primarily at those wishing to become professional architects, it also offers those in disciplines related to architecture (from archaeology to stage design, garden design to installation art), a clear and accessible insight into the workings of this rich and fascinating subject. With copious illustrations from his own notebooks, the author dissects examples from around the world and all periods of history to explain underlying strategies in architectural design and show how drawing may be used as a medium for analysis"--
How analysis helps a design -- Architecture as identification of place -- Basic elements of architecture -- Modifying elements of architecture -- Elements doing more than one thing -- Using things that are there -- Primitive place types -- Architecture as making frames -- Temples and cottages -- Geometries of being -- Ideal geometry -- Themes in spatial organisation: Space and Structure -- Parallel Walls -- Stratification -- Transition, Hierarchy, Heart -- Occupying the In-Between -- Inhabited Wall -- Refuge and Prospect -- Postscripts -- Case studies.
Includes bibliographical references (pages 311-317) and index.
Keywords: Architectural design; Architectural design -- Case studies; ARCHITECTURE / General